Economic Growth, Poverty, and Household Welfare in Vietnam - Glewwe, Paul; Agrawal, Nisha; Dollar, David (Washington, DC: World Bank, 2013)
Viet Nam is an economic success story - it transformed itself from a country in the 1980s as one of the poorest in the world, to a country in the 1990s with one of the world's highest growth rates. With the adoption of a new market-oriented policies, Viet Nam averaged an economic growth rate of 8 percent per year from 1990 to 2000, a growth rate accompanied by a large reduction in poverty, stemming from significant increases in school enrollment, and a rapid decrease in child malnutrition. The book uses an unusually rich set of macroeconomic, and household survey data, to examine several topics: the causes of the economic turnaround, and prospects for future growth; the impact of economic growth on household welfare, as measured by consumption expenditures, health, education, and other socioeconomic indicators; and, the nature of poverty in Viet Nam, and the effectiveness of government policies, intended to reduce same. Although the country's past achievements are impressive, future progress is by no means ensured.